Analisis Kebijakan Indonesia Terhadap Regulasi UNESCO Convention 2001 - Maulana Satria Wibowo; Andi Akhmad Basith Dir (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
UNESCO has been recommending the “UNESCO Convention on the Protection of the Underwater Cultural Heritage” or commonly referred to as the 2001 UNESCO Convention as a conservation procedure for Underwater Cultural Heritage (UCH) which prioritizes the protection of historical, cultural and scientific values. Through several conferences and discussions, UNESCO has always encouraged countries that have strategic sea areas to immediately ratify by considering the potential underwater relics in its territories. The Republic of Indonesia, as the biggest archipelagic country nowadays has not ratified the convention. Even though, this research argues that Indonesia does not have strong regulations and always experiences obstacles in securing Underwater Cultural Heritage these days. This research is trying to seek and solve the research question with all the existing vulnerabilities, why until now Indonesia has not ratified the 2001 UNESCO Convention. This research will identify the background factors that make Indonesia reluctant and have not taken action to ratify the convention. For the tools analyzing in this case study, this research will use Decision Making Approach by Graham T. Allison, with 2 approach models namely Rational Actor Model and Organizational Model. This study found that rational factors were the reason for Indonesia not to ratify the 2001 UNESCO Convention.